Dampak Sosial Ekonomi Alih Fungsi Lahan Pertanian Bagi Anggota Subak Kerdung Di Kota Denpasar - Dewi, Ida Ayu Listiya; Sarjana, I Made; Pradnyawathi, Ni Luh Made (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2016)
Growth of Denpasar City gives negative effect to the agriculture land. Growth development in city are the major cause of wetland function conversion. City farmer become victim towetland function transfer. This research aim are to photographing the impact of wetland function conversion, especially in SubakKerdung, North Denpasar. The research site selection is done by purposive. The sample used are 28 peoples,  selected by purposive. Data analysis used in this research are descriptive qualitative. Based on the research, social impact is felt by farmers members in SubakKerdung are dwindling water supply because the breakdown of the water chanel due to housing construction in agriculture land. Many household waste carried into waterways and clogs the waterways. Waters usually inundate the field when the waters are not used. The household waste that inundated and water pollution due to textile industry make the environment dirty and malodorous. The farmers complained about itchi when they go to the field. Social conflict raised with land developers. Economic conflicts raised due to wetland function conversion are emerging new jobs as an alternative to from the lost income. New jobs emerging are rice mill, poultry, trade, parking attendants, and driver.
Keywords: conversion, social impact, economic impact